Pengembangan Bahan Ajar Etnomatematika Mengunakan Model RME Materi Pecahan untuk Meningkatkan Hasil Belajar Siswa Kelas IV SDN 13 Tambun Sungkean: Penelitian - Insa Gultom; Ahmad Landong (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The research conducted aims to develop ethnomathematics teaching materials using the RME model to improve the learning outcomes of fourth grade students of SDN 13 Tambun Sungkean and to determine the validity, practicality and effectiveness of the developed teaching materials. In this study, the researcher used the ADDIE development procedure consisting of 5 stages. The instrument used to determine the validity, practicality and effectiveness of ethnomathematics teaching materials using the RME model to improve the learning outcomes of fourth grade students of SDN 13 Tambun Sungkean, namely a questionnaire. The validity of ethnomathematics teaching materials using the RME model of fraction material developed obtained a percentage of 90% with the criteria of